Which factors predict parametrial involvement in early stage cervical cancer? A Turkish multicenter study. (December 2019) - Kilic, Cigdem; Cakir, Caner; Yuksel, Dilek; Tokgozoglu, Nedim; Comert, Gunsu Kimyon; Karalok, Alper; Ureyen, Isin; Turkmen, Osman; Boyraz, Gokhan; Tasci, Tolga; Tekin, Ozlem Moraloglu; Turan, Taner
Abstract: Objective: To evaluate the clinical and pathological factors for predicting the parametrial involvement (PI) in early stage cervical cancer. Study design: This study included 406 patients with type III radical hysterectomy + pelvic ± para-aortic lymphadenectomy and FIGO stage I and II cervical adenocarcinoma, squamous type, and adenosquamous type cervical cancer. Results: The entire cohort of patients had lymphadenectomy performed. Early stage cervical cancer patients were evaluated. FIGO 2014 stage, uterine invasion, LVSI, surgical border involvement, vaginal metastasis, stromal invasion and lymph node metastasis were found to be effective for PI on univariate analyses. However; age, tumor type and tumor size did not determine the parametrial invasion. LVSI (HR: 4.438, 95%CI: 1.771–11.121; p = 0.001 ), lymph node metastases (HR: 2.418, 95%CI: 1.207–4.847; p = 0.013 ) and vaginal involvement (HR: 4.109, 95%CI: 1.674–10.087; p = 0.02 ) are independent prognostic factors on multivariate analysis. Conclusion: Lymph node metastases, LVSI and surgical border involvement are independent prognostic factors for PI in early stage cervical cancer patients. Therefore, less radical surgical approaches for early stage tumors with no nodal spread, negative LVSI and no surgical border involvement are applicable.